Pengendalian Kualitas Produk Cacat Spun pile di PT. X dengan Menggunakan Metode Six Sigma - Himawan, Diva Hazimah Putri; Herwanto , Dene (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
Product quality is important in the production process in a company. Product quality control is key in winning the competition in the business world. One company that must always produce good quality products is PT. X. This study aims to determine the sigma level and provide recommendations for improvements to the production process of one of its products, namely spun pile. This research uses the six sigma method with the concept of DMAIC. The calculation of the sigma level gets a result of 4.262. Then from the Pareto chart it is known that the highest type of defect is crack. Furthermore, with a fishbone diagram, improvements are focused on method factors, namely adding SOP in the demoulding process, increasing the demoulding process floor area, and making a wood replacement schedule for stocking in the stockyard. Keywords: DMAIC, Fishbone Diagram, Quality, Six sigma